Optimizing Students’ Performance through Artificial Intelligence (AI) Technology: A Gamified Approach to Smart Learning Environment - Balaquiao, Ely Christian (The Indonesian Institute of Science and Technology Research, 2024)
This study tested the application of Artificial Intelligence (AI) technology to optimize students' performance within a smart learning environment, employing a gamified approach. The study assessed the effectiveness of integrating AI-driven gamification techniques in Mathematics in the Modern World classes and their impact on engagement, motivation, and academic achievement. It utilized a descriptive-evaluative and quasi-experimental design. Descriptive analysis gauged student performance in pretest and posttest, while evaluative design identified differences between control and experimental groups. Quasi-experimental design assessed if the treatment caused changes in the dependent variable, measuring pre- and post-treatment variables to observe significant differences. Results showed that there was a significant difference in students’ performance in Mathematics in the Modern World classes after the integration of Artificial Intelligence (AI) technology in the instruction in the experimental group. The noteworthy improvement in student performance following the integration of Artificial Intelligence (AI) technology underscores its positive impact on enhancing instructional effectiveness, advocating for broader implementation and exploration in educational settings. However, the study's findings may be context-specific, and generalizability could be limited, as variations in educational settings and technological infrastructure may influence the effectiveness of AI-integrated gamified approaches.